PRACTICAL TRAINING OF STUDENTS BY PROFESSION AS A MEANS OF TRAINING A COMPETENT TEACHER OF LABOR EDUCATION (Pedagogy of Higher and Secondary Education, 2022)
Article is devoted to definition of the purposes and maintenances (contents) of technological practice of studenis of faculties ofpreparation of teachers of labour training in conditions of step higher edtucation which has contiuous character and provides efective jormation at them corresponding the comperence.
Keywords: practical prepavation of students; step formation (education); technological practice; the teacher of labour training